Factors Influencing the Design and Use of Performance Measurement Systems in the Malaysian Electrical and Electronics Industry - Ong, Tze San; Teh, Boon Heng (Universiti Putra Malaysia, 2009)
Data from a questionnaire survey covering 149 electronics and electrical manufacturing companies in Malaysia are used to identify the factors influencing the design and use of performance measurement systems (PMSs). Factor analysis identified organizations’ contextual factors as potential contingency variables that include: (1) two dimensions of organisational profile—company size and ownership types; (2) four dimensions of organisational culture—knowledge and innovation, learning culture, absorptive capability and employee’s understanding and learning; (3) four dimensions of organisation strategy—stakeholder focus, pricing and distribution, marketing segmentation and growth; and (4) four dimensions of technology—information technology and customisation, volume and variety of product and process, information and technological advancement, and product complexity.